Systemic illiquidity in the interbank network - Gerardo Ferrara; Sam Langfield; Zijun Liu; Tomohiro Ota (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
We study systemic illiquidity using a unique dataset on banks' daily cash flows, short-term interbank funding and liquid asset buffers. Failure to roll-over short-term funding or repay obligations when they fall due generates an externality in the form of systemic illiquidity. We simulate a model in which systemic illiquidity propagates in the interbank funding network over multiple days. In this setting, systemic illiquidity is minimised by a macroprudential policy that skews the distribution of liquid assets towards banks that are important in the network.
Keywords: D85; E44; E58; G28; 330; Systemic risk; liquidity regulation; macroprudential policy